2019
DOI: 10.1051/kmae/2019018
|View full text |Cite
|
Sign up to set email alerts
|

Dietary niche divergence between two invasive fish in Mediterranean streams

Abstract: Clarifying the mechanisms associated with the coexistence of invasive species is important to understand the overall impact of multiple invasions on recipient communities. Here we examined whether divergence or convergence in dietary niche occurred when invasive Lepomis gibbosus and Australoheros facetus coexist in Iberian streams. We used stomach content analyses to determine dietary niche composition, width, and overlap in allopatric and sympatric counterparts in the Lower Guadiana throughout the dry-season.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
2
5
0
Order By: Relevance
“…A larger number of iterations was used in order to reduce stress values to <0.2, as the standard approach resulted in lack of component convergence; this was possibly due to low sample size. A follow up analysis of similarity (ANOSIM) was attempted, but trust in the results was not satisfactory and therefore was not included, following Gkenas et al (2019) [33].…”
Section: = × 100mentioning
confidence: 99%
“…A larger number of iterations was used in order to reduce stress values to <0.2, as the standard approach resulted in lack of component convergence; this was possibly due to low sample size. A follow up analysis of similarity (ANOSIM) was attempted, but trust in the results was not satisfactory and therefore was not included, following Gkenas et al (2019) [33].…”
Section: = × 100mentioning
confidence: 99%
“…given Several studies have identified trophic niche shifts from allopatry to sympatry, for instance between morphologically similar fish (Gkenas et al, 2019;Schmitt & Coyer, 1983) and reptile species (Huey et al, 1974;Klawinski et al, 1994). However, in bats, previous coexistence studies looking at trophic ecology only focused on sympatric or syntopic populations, and rarely found evidence of trophic resource partitioning.…”
Section: Trophic Partitioning Across Spatial Scalesmentioning
confidence: 99%
“…Several studies have identified trophic niche shifts from allopatry to sympatry, for instance between morphologically similar fish (Gkenas et al, 2019;Schmitt & Coyer, 1983) and reptile species (Huey et al, 1974;Klawinski et al, 1994). However, in bats, previous coexistence studies looking at trophic ecology only focused on sympatric or syntopic populations, and rarely found evidence of trophic resource partitioning.…”
Section: Trophic Partitioning Across Spatial Scalesmentioning
confidence: 99%